Tourism : A Modern Synthesis - Page, Stephen J., 1963- and Connell, Joanne (Australia Thomson, 2006)
Focuses on the development and management of tourism in an international context. This book includes all of the issues in tourism such as the impact of terrorism and crime, epidemics and tourism, low-cost airlines, special interest tourism and includes many case studies from diverse and exciting tourism destinations.
Include Illustration, Map, Table, References and Index
Keywords: Tourism -- Cities and towns